Trial by television [videorecording] - Gallagher, Paul.; Rosenbaum, Steven; Sommers, Cardine; Broadcast News Network, Inc.; The Arts and Entertainment Network (New York). (New York A & E Network [producer], 1993)
Explores both sides of the issue on trial by television by interviewing victims and experts. This investigative report provides stories of actual cases that have been complicated by too much media attention.
Documentary.
VHS.
Host, Bill Kurtis; Editors, Christofer Wagner Steven Mandes; executive producer for A%E, Michael Cascio ; writer/producer for Investigative Reports, Bob Harris.
Keywords: Crime and the television; Trials -- United States